Plant-Derived Exosomes for Enzyme Delivery in Prostate Cancer: A Narrative Perspective and Conceptual Roadmap - Dincer, Zeynep Yaren; Ziksahna, Kaan; Ihlamur, Murat (SPRINGERNATURE, 2026)
BackgroundPlant-derived extracellular vesicles (P-EVs; hereafter exosomes) are biocompatible, low-immunogenic, and scalable nanocarriers with inherent organotropism. Distinct lipid/protein composition and biogenesis may provide technical advantages over mammalian exosomes for loading and delivering therapeutic cargo. However, while persuasive in vitro/in vivo data support P-EV delivery of chemotherapeutics and nucleic acids, enzyme-loaded P-EVs for targeted cancer therapy-particularly in prostate cancer-remain an underexplored niche.ObjectiveThis narrative perspective review synthesizes the technical basis, loading strategies, and translational prospects of using P-EVs specifically as enzyme-delivery platforms in prostate cancer. We highlight L-asparaginase (to exploit asparagine dependence associated with TP53 alterations) and protease-axis inhibitor proteins/peptides (e.g., targeting MMPs, cathepsins, serine proteases) as rational cargos for repeat, targeted dosing.MethodsWe narratively compare P-EVs versus mammalian exosomes with respect to biocompatibility, manufacturability, and suitability for enzyme cargo; appraise passive (incubation) and active (sonication, electroporation, extrusion, chemical poration) loading with emphasis on preserving activity of labile enzymes; and propose a conceptual experimental roadmap, rather than a fixed laboratory protocol, comprising: (i) nanoparticle tracking analysis/dynamic light scattering and cryo-TEM for vesicle integrity; (ii) Western blotting for EV markers with appropriate negative-marker controls plus cargo detection; (iii) cargo-specific catalytic assays; and (iv) biodistribution and efficacy analyses within the tumor microarchitecture.ResultsExisting evidence supports efficient P-EV-mediated delivery of small molecules and nucleic acids; targeted enzyme therapy is nascent but conceptually strong. Within this framework, L-asparaginase and protease-axis inhibitors emerge as rational cargos for prostate cancer, with potential for intratumoral enrichment and repeat dosing while minimizing systemic toxicity. Loading choice and rigorous QC are critical to maintain vesicle integrity, enzyme activity, and favorable distribution.ConclusionP-EV-based enzyme delivery may enhance efficacy and reduce off-target toxicity in prostate cancer. We outline a bench-to-bedside roadmap that prioritizes GMP-compliant isolation, optimization of loading efficiency and cargo integrity, and robust in vivo biodistribution, efficacy, and safety under repeat dosing. By explicitly focusing on enzyme delivery for prostate cancer-rather than broader P-EV applications-this review delineates a specific, underexplored translational pathway for future experimental studies.
Keywords: Plant-derived extracellular vesicles (P-EVs); Exosome; Enzyme delivery; L-asparaginase; Protease inhibitors; Prostate cancer; ACUTE LYMPHOBLASTIC-LEUKEMIA; EXTRACELLULAR VESICLES; DRUG-DELIVERY; STEM-CELLS; NANOPARTICLES; ASPARAGINASE; INHIBITION; DISEASE; MATRIX; GROWTH; General & Internal Medicine